2006
DOI: 10.1016/j.neulet.2006.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kinetic redundancy on hand digit control in children with DCD

Abstract: We investigated finger strength and the ability to control digit force/torque production in children with Developmental Coordination Disorder (DCD) using manipulative tasks with different kinetic redundancies (KNR). Age-related changes in finger strength and finger force/torque control in typically developing (TD) children were also examined to provide a developmental landscape that allows a comparison with children with DCD. Forty-eight TD children (7-, 9-, and 11-year-olds) and sixteen 9-year-old children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 25 publications
7
44
0
3
Order By: Relevance
“…However, when participants were asked to control torque at different submaximum levels, there was greater motor response variability. these results concur with findings of previous studies for tasks involving finger-pressure strength control 26 , two-fingered prehension in pinch 14 and torque in lateral pinch 4,19 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, when participants were asked to control torque at different submaximum levels, there was greater motor response variability. these results concur with findings of previous studies for tasks involving finger-pressure strength control 26 , two-fingered prehension in pinch 14 and torque in lateral pinch 4,19 .…”
Section: Discussionsupporting
confidence: 93%
“…two tasks involving isometric supination torque (tq) in lateral pinch (using the thumb pad and the radial side of the second phalanx of the index finger) were assessed with a customized torque transducer 4,18,19 . Subjects were asked to perform two isometric tasks: maximum voluntary torque in lateral pinch (tq maX ) and constant and continuous torque in lateral pinch (tq ConSt ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manifold is approximated linearly by the null space spanned by the orthonormal basis vector, e(Y), solving the following equation. Greater DV values represent a greater kinetic synergy between hand-pen contact forces (Oliveira et al, 2006;Shim et al, 2008). In other words, DV quantifies how well the four individual force components compensate for each other's errors to achieve the constant trajectory of circle drawing.…”
Section: ½Umentioning
confidence: 99%
“…However, the same structure may also present control challenges to the CNS because of the extremely high motor redundancy inherent in its system (Chao and An, 1978;Dul et al, 1984;Oliveira et al, 2006). For example, when a hand holds a pen with multiple fingers, the motor task becomes kinetically redundant because there are more contact forces than the forces minimally necessary for the movement outputs of the pen (e.g., pen-tip force) (Shim et al, 2005a;Oliveira et al, 2006;Fernandes and Chau, 2008). Previous studies on multi-finger pressing and grasping have shown that the CNS prioritizes some sub-tasks critical for the achievement of redundant motor tasks to utilize the redundancy (Shim et al, 2003Gorniak et al, 2009;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%